The Role of Calcium-Permeable AMPARs in Long-Term Potentiation at Principal Neurons in the Rodent Hippocampus - Park, Pojeong; Kang, Heather; Sanderson, Thomas M.; Bortolotto, Zuner A.; Georgiou, John; Zhuo, Min; Kaang, Bong-Kiun; Collingridge, Graham L. (Frontiers in Synaptic Neuroscience, 2018)
Long-term potentiation (LTP) at hippocampal CA1 synapses is classically triggered by the synaptic activation of NMDA receptors (NMDARs). More recently, it has been shown that calcium-permeable (CP) AMPA receptors (AMPARs) can also trigger synaptic plasticity at these synapses. Here we review this literature with a focus on recent evidence that CP-AMPARs are critical for the induction of the PKA- and protein synthesis-dependent component of LTP.